J-pouch vs. side-to-end anastomosis after hand-assisted laparoscopic low anterior resection for rectal cancer: A prospective randomized trial on short and long term outcomes including life quality and functional results - ATICI, ALİ EMRE (ELSEVIER SCIENCE BV, 2017)
Purpose: To analyze the outcomes of j-pouch and side-to-end anastomosis in rectal cancer patients treated with laparoscopic hand-assisted low anterior resection. Methods: Prospective trial on cases randomized to have a colonic j-pouch or a side-to-end anastomosis after low anterior resection. Demographics, characteristics of disease and treatment, perioperative results, and functional outcomes and life quality were compared between the groups. Results: Seventy four patients were randomized. Reservoir creation was withdrawn in 17 (23%) patients, mostly related to reach problem (n = 11, 64.7%). Anastomotic leakage rate was significantly higher in j-pouch group (8 [27.6%] vs. 0, p = 0.004). Stoma closure could not be achieved in 16 (28.1%) patients. Life quality and functional outcomes, measured 4, 8 and 12 months after the stoma reversal, were similar. Conclusions: Colonic j-pouch and side-to-end anastomosis are similar regarding perioperative measures including operation time, rates of postoperative complications, reoperation and 30-day mortality, and hospitalization period except anastomotic leak rate, which is higher in j-pouch group. Postoperative aspects are not different in patients receiving either technique including functional outcomes and life quality for the first year after stoma closure. In our opinion, both techniques may be preferred during the daily practice while performing laparoscopic surgery; but surgeons may be aware of a possibly higher anastomotic leak rate in case of a j-pouch. (C) 2017 IJS Publishing Group Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: J-pouch; Rectal cancer; Ileostomy; Life quality; Anastomosis; COLONIC J-POUCH; TOTAL MESORECTAL EXCISION; RECONSTRUCTION; COLOPLASTY; METAANALYSIS; STRAIGHT; INDEX